Costa Rica : 2017 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights the growth of Costa Rica's economy at its estimated trend rate of about 4.25 percent and an essentially closed output gap. Headline inflation turned positive again in the second half of 2016 and is rising moderately, with both headline and core indicators still below the 2-4 percent target range. The colon has been depreciating moderately since mid-2016, while reserves have declined despite the narrowing in the current account deficit. In 2017, growth is anticipated to slow marginally to 4 percent, driven by weaker terms of trade and more stringent financial conditions.